2011
DOI: 10.1007/s10854-011-0568-6
|View full text |Cite|
|
Sign up to set email alerts
|

Studies of electrical resistivity and magnetic properties of nanocrystalline CoFeCu thin films electrodeposited from citrate-added baths

Abstract: In this study, nanocrystalline CoFeCu thin films were electrodeposited at different current densities from baths with natural pH (around 5.2) and containing 20 g/L citrate sodium. The relationship of films structure with soft magnetic properties and electrical resistivity, which are required for new generation magnetic head core, were investigated. SEM, EDS, XRD, TEM, VSM and four probe-point methods were used for characterization of the deposited films. The deposited films exhibited very uniform and homogenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Additionally, there is no reflection from the diffraction peak of the bcc phase structure of Fe in the XRD patterns of the deposits with low Fe contents of 4.1 at.% and 7.8 at.%, as can be seen from Figures 4a and 4b, respectively. Similarly, no reflection from the diffraction peak of the bcc phase structure of Fe was observed in previous studies carried out with electrochemically deposited Co-Fe-Cu ternary films when the Fe content within the films was lower than 11 at.% [4] and 14 at.% [8]. As a result, we reveal that the phase structure changes from a mixture of hcp Co and fcc/hcp Co to a mixture of fcc/hcp Co and bcc Fe with increasing Fe content within the films, as also summarized in Table 1.…”
Section: Resultssupporting
confidence: 57%
See 4 more Smart Citations
“…Additionally, there is no reflection from the diffraction peak of the bcc phase structure of Fe in the XRD patterns of the deposits with low Fe contents of 4.1 at.% and 7.8 at.%, as can be seen from Figures 4a and 4b, respectively. Similarly, no reflection from the diffraction peak of the bcc phase structure of Fe was observed in previous studies carried out with electrochemically deposited Co-Fe-Cu ternary films when the Fe content within the films was lower than 11 at.% [4] and 14 at.% [8]. As a result, we reveal that the phase structure changes from a mixture of hcp Co and fcc/hcp Co to a mixture of fcc/hcp Co and bcc Fe with increasing Fe content within the films, as also summarized in Table 1.…”
Section: Resultssupporting
confidence: 57%
“…On the other hand, the absence of fcc Cu peaks in all XRD patterns can probably be attributed to the low Cu content within the films (about 3 at.%). In a previous study, the reflection from the fcc Cu diffraction peak was not observed when the Cu content was lower than 15 at.% [4]. Additionally, there is no reflection from the diffraction peak of the bcc phase structure of Fe in the XRD patterns of the deposits with low Fe contents of 4.1 at.% and 7.8 at.%, as can be seen from Figures 4a and 4b, respectively.…”
Section: Resultsmentioning
confidence: 59%
See 3 more Smart Citations